Efektivitas Dakwah Majelis Taklim Madhul Musthafa dalam Merubah Perilaku Remaja di Desa Montong Are Kec. Kediri Lombok Barat - Moh. Zarkani (P3M STID Mustafa Ibrahim Al-Ishlahuddiny Kediri Lombok Barat, 2024)
Da'wah will face increasingly complex problems along with the progress of rolling civilization, which appears in increasingly complex da'wah works. Many perspectives of da'i who are most difficult for them to preach are teenagers, because their thinking is still unstable and tends to be stubborn. The role of the da'wah leader will greatly determine the color of the activities to be carried out, thus a da'wah leader must be able to provide inspiration for teenagers so that they are willing to think long and religiously. The form of da'wah carried out as a call or invitation to awareness, or an effort to change a bad situation into a better and perfect situation for both individuals and society, especially for teenagers. The study aims to determine the Effectiveness of Da'wah of the Majlis Taklim Madhul Mushafa in changing the behavior of teenagers using Hadroh in Montong Are Village, Kediri District, West Lombok Regency. This study uses a quantitative research type, with the approach method used is a survey with a data collection technique using a questionnaire distributed to teenagers in Montong Are Village, Kediri District, West Lombok. To find out whether there is the effectiveness of da'wah of the Majlis Madhul Musthafa in changing the behavior of teenagers, the data collected will be analyzed using statistical methods with the help of the IBM Statistical Program For Social Science (SPSS) application. Here the researcher uses the SPSS version 24 application.